Boosting biodiversity action through agroecology: Guidance for developing and updating national biodiversity strategies and action plans - Global Alliance for the Future of Foods; Biovision Foundation; WWF International; Bioversity International and International Center for Tropical Agriculture; Agroecology Coalition (2024)
This document provides guidance for integrating agroecology and food systems into the development and implementation of National Biodiversity Strategies and Actions Plans (NBSAPs) in alignment with the KunmingMontreal Global Biodiversity Framework (GBF). The goal of this Guidance is to support implementation of the GBF at the national level while strengthening policy coherence between the GBF and international goals and targets on food systems, including Sustainable Development Goal (SDG) 2 (End hunger, achieve food security and improved nutrition and promote sustainable agriculture), and United Nations Food Systems Summit (UNFSS) national pathways to sustainable food systems. In addition, this Guidance sheds light on the opportunities and challenges of coordinated national-level policy planning and implementation. Integrating agroecology into NBSAPs is an opportunity to address biodiversity while simultaneously advancing other international targets, including those related to climate change, desertification, disaster risk reduction, health, nutrition, combating hunger, and reducing poverty.